The Cognition Role to Understanding Planning and Architectural Production - Ahmed S. Al-Khafaji; Nadia A. Al-Salam; Tuqa R. Alrobaee (Civil Engineering Journal, 2021)
This paper focuses on the concept of cognition and its clarification in the light of Islamic epistemology. Knowledge passes through two essential parts: conception and assent. Conception explains simple knowledge, while assent explains knowledge involving a judgment. The paper proceeded with the identification of the problem of relationship blurring between cognition and knowledge. The external and inner senses have explained the relationship between the stages of knowledge and cognition. The external senses receive stimuli and form primary conceptions. These conceptions transfer to the first part of the inner senses, which is common sense; it collects the sensations and transmits them to pictorial power. Secondary conceptions are formed, accompanied by feeling. Then, the estimative power role emerges in imparting meaning to be stored in memory, here knowledge is suspicion, and the perception is achieved. Finally, the images reach the thinking power to impart the specific meaning of the image, which constitutes cognition. Using the Hagia Sophia Case Study, the paper reached important indices in clarifying the cognition stages and understanding of planning and architectural production. These indices were represented by: color, scale, lighting, the harmony of the building with its surroundings, and the meanings associated with cultural, social, and civilized values. Doi: 10.28991/cej-2021-03091715 Full Text: PDF